Properties of sugarcane bagasse/ poly(vinyl chloride) composites after various treatments - Salit, Mohd Sapuan; Abdan, Khalina; Yunus, Robiah; Wirawan, Riza (2011)
The properties of sugarcane filled poly(vinyl chloride) (PVC) composites after various treatments were studied. The studied chemical treatments were fiber treatment with benzoic acid, fiber treatment with sodium hydroxide, and the incorporation of poly[methylene(polyphenyl) isocyanate] (PMPPIC) as coupling agent. Results showed that chemical-treated composites obtain higher tensile strength and modulus as compared to untreated sugar-free bagasse/PVC composite. Among the three chemical treatments, the incorporation of PMPPIC gave the highest tensile strength and modulus. Both tensile strength and modulus of treated composite, however, are lower than those of untreated sugarcane bagasse (SB)-filled composite when unwashed bagasse, which contained sugar, was used. It is suspected that sugar may contribute to the tensile strength and modulus of the composite and hence, the SB can be used as reinforcing agent without further chemical treatment.